Physiological and transcriptional studies reveal Cr(VI) reduction mechanisms in the exoelectrogen Cellulomonas fimi Clb-11 - Cao, Lianbin; Lu, Mingguo; Zhao, Mengrui; Zhang, Yifan; Nong, Yiping; Hu, Mengxue; Wang, Ya; Li, Tongbiao; Chen, Fujia; Wang, Mingcheng; Liu, Junhe; Li, Enzhong; et al. (Frontiers in Microbiology, 2023)
A facultative exoelectrogen, Cellulomonas fimi strain Clb-11, isolated from polluted river water, could generate electricity in microbial fuel cells (MFCs) with carboxymethyl cellulose (CMC) as the carbon source, and the maximum output power density was 9.81 ± 0.58 mW·m-2. In addition, Clb-11 was capable of reducing Cr(VI) to Cr(III). At concentrations less than 0.5 mM in Luria-Bertani (LB) medium, Cr(VI) could be completely reduced by Clb-11. However, the Clb-11 cells swelled significantly in the presence of Cr(VI). We employed transcriptome sequencing analysis to identify genes involved in different Cr(VI) stress responses in Clb-11. The results indicate that 99 genes were continuously upregulated while 8 genes were continuously downregulated as the Cr(VI) concentration increased in the growth medium. These genes were mostly associated with DNA replication and repair, biosynthesis of secondary metabolites, ABC transporters, amino sugar and nucleotide sugar metabolism, and carbon metabolism. The swelling of Clb-11 cells might be related to the upregulation of the genes atoB, INO1, dhaM, dhal, dhak, and bccA, which encode acetyl-CoA C-acetyltransferase, myo-inositol-1-phosphate synthase, phosphoenolpyruvate-glycerone phosphotransferase, and acetyl-CoA/propionyl-CoA carboxylase, respectively. Interestingly, the genes cydA and cydB related to electron transport were continuously downregulated as the Cr(VI) concentration increased. Our results help elucidate the global bacterial response to Cr(VI) and provide a functional exoelectrogen strain for the removal of Cr(VI) in practical applications, such as in MFCs.